2006
DOI: 10.1007/s00606-005-0373-x
|View full text |Cite
|
Sign up to set email alerts
|

Floral ontogeny of Cneorum tricoccon L. (Rutaceae)

Abstract: Abstract. The floral ontogeny of the Spurge olive (Cneorum tricoccon L.) is studied by means of scanning electron microscopic observations. Special attention is paid to the sequence of initiation of the floral parts, the occurrence of septal cavities, and the development of the nectariferous tissue. The nectary disc arises as a receptacular outgrowth below the ovary and independently from stamen development. By the extensive growth of this voluminous androgynophore, stamen filaments become enclosed by nectary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…A shared feature of all three genera studied here is the presence of postgenitally united carpel tips (style and stigma), as known from most other Rutaceae (Endress et al, 1983;Ramp, 1988;Caris et al, 2006;Wei et al, 2012). In Galipeinae, it was first observed in E. brasiliensis by Ramp (1988).…”
Section: Partially Apocarpous Gynoecium and Its Consequences: Compitumentioning
confidence: 53%
“…A shared feature of all three genera studied here is the presence of postgenitally united carpel tips (style and stigma), as known from most other Rutaceae (Endress et al, 1983;Ramp, 1988;Caris et al, 2006;Wei et al, 2012). In Galipeinae, it was first observed in E. brasiliensis by Ramp (1988).…”
Section: Partially Apocarpous Gynoecium and Its Consequences: Compitumentioning
confidence: 53%
“…Both N. pulverulenta and C. tricoccon have been described as andromonoecious (Tébar & Llorens, 1997) but N. pulverulenta might be (functionally) androdioecious (Lorenzo & al., 2003). Additionally, septal cavities in the ovules were found in C. tricoccon but are absent in N. pulverulenta (Schmid, 1985;Caris & al., 2006). Apart from these characters, the two species are very much alike.…”
Section: Discussionmentioning
confidence: 98%
“…Erdtman but this has been ignored by most recent authors (e.g. Caris & al., 2006;Appelhans & al., 2008;Groppo & al., 2008) as well as by the APG (Stevens, 2001 onwards).…”
Section: Discussionmentioning
confidence: 99%
“…In Rutaceae, the most early-diverging lineage Cneoroideae is represented by haplostemony [ 1 ]. Most genera in this subfamily have small haplostemonous flowers like Cneorum [ 51 ]. The ancestral state reconstruction also showed that haplostemony is the ancestral character in Rutaceae.…”
Section: Discussionmentioning
confidence: 99%